Synthesis, HPLC and NMR studies on axially chiral pyridine compounds as potential bidentate N,N'-ligands - Işıkgör, Furkan Halis. (Thesis (M.S.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2012., 2012)
In this study, axially chiral enantiomeric and diastereomeric 2-arylimino-3-aryl-thiazolidine-4-ones have been synthesized and their stereostructures have been investigated. In these compounds, the rotation around N3-aryl bond is restricted resulting in axial chirality. Therefore, M and P enantiomers or RM, RP and SM, SP diastereomers exist. Enantiomeric and diastereomeric isomers of the compounds have been investigated by 1H-NMR and HPLC. In 3-(pyridin-2-yl)-2-(pyridin-2-ylimino)thiazolidine-4-one, it was found that the rotation around N3-aryl bond is too fast to make the enantiomeric isomer separation observable by enantioselective HPLC. On the other hand, the interconversion rate between the enantiomers of 3-(3-methylpyridin-2-yl)-2-(3-methylpyridin-2-ylimino)thiazolidine-4-one and the energy barrier for this compound have been determined by thermal racemization of the micropreparatively resolved enantiomers. Rotational barrier of the diastereomers of 5-methyl-3-(3-methylpyridin-2-yl)-2-(3-methylpyridin-2-ylimino) thiazolidine-4-one has also been determined by following the interconversion between the unequally populated diastereomers with time by HPLC. Also, 3-(3-methylpyridin-2-yl)-2-(3-methylpyridin-2-ylimino)thiazolidine-4-thione was synthesized by converting the C-4 carbonyl oxygen to a sulphur atom via the Lawesson Reagent. It was found that replacing one C-5 proton with a methyl group decreased the rotational barrier by 2.2 kJ/mol. On the other hand, replacing C-4 carbonyl oxygen with a sulphur atom increased the barrier by 18.3 kJ/mol.
Keywords: Pharmacology.; Chemistry, Physical and theoretical.; Chemistry, Organic.